Features of transbronchial lung cryobiopsy‐diagnosed fibrotic hypersensitivity pneumonitis. (17th November 2022) - Zhan, Xi; Du, Yingzhen; Luo, Jiang; Que, Yifan; Hu, Chao; Xu, Lili; Wang, Zhen; Wu, Yanbing; Jin, Mulan; Zheng, Chunming; Gao, Yanhong; Chang, Christopher; et al.
Abstract: Background: Hypersensitivity pneumonitis (HP) is a common type among all the interstitial lung diseases, and transbronchial lung cryobiopsy is an alternative diagnostic technique for interstitial lung diseases. In this study, we describe the clinical and pathological features of fibrotic hypersensitivity pneumonitis diagnosed with transbronchial lung cryobiopsy (TBLC). Methods: A total of 46 diffused parenchyma lung disease (DPLD) patients received TBLC were included in this study. Medical records including medical history spirometry examinations, 6‐min walk test (6MWT) results, high resolution computed tomographic (HRCT) scans, BAL, and histopathology were collected. Results of HRCT and histopathology were compared and classified, especially. Results: Sixteen patients were diagnosed with fibrotic HP, the mean age of whom was 56.3 ± 12.1 years, and 62.5% of them were male. Three of the 16 patients had been misdiagnosed as tuberculosis and received antituberculosis medications, five patients had been diagnosed as unclassifiable pulmonary fibrosis, and five patients had been diagnosed as idiopathic pulmonary fibrosis (IPF). Thirteen (81.3%) patients had a normal lymphocyte count in BAL. The pathological features of usual interstitial pneumonia (UIP) were detected in 11 (68.8%) of the cases, poor defined granulomatous was detected in nine (56.3%) of the cases, and bronchiolocentric fibrosis was detected in two (12.5%) of the 16 cases. Conclusions: Fibrotic hypersensitivity pneumonitis should be included in differential diagnosis of pulmonary fibrosis. Pathological characteristics of fibrotic hypersensitivity pneumonitis could be demonstrated from cryobiopsy lung tissue. TBLC is recommended as an alternative diagnostic technique, which may improve the specificity of hypersensitivity pneumonia detection, and UIP is the most frequent pathological finding. Abstract : This study describes the clinical and pathological features of fibrotic hypersensitivity pneumonitis diagnosed with transbronchial lung crybiopsy. Usual interstitial pneumonia was the most frequent pathological finding of fibrotic hypersensitivity pneumonitis. Transbronchial lung crybiopsy could be considered as a diagnostic technique for fibrotic hypersensitivity pneumonitis.